Distance travelled to tertiary pediatric care impacts care-seeking behavior and hospital outcome in Vietnam - David A Rollins; Timothy T Xu; Viet Hoang; Khang Tuan Hoang; Sarah S Kang; Toan Ngoc Pham; Duy Ngoc Le; Yves Ouellette (Journal of Global Health Reports)
# Background